2018
DOI: 10.7554/elife.29539
|View full text |Cite
|
Sign up to set email alerts
|

Sumoylation promotes optimal APC/C activation and timely anaphase

Abstract: The Anaphase Promoting Complex/Cyclosome (APC/C) is a ubiquitin E3 ligase that functions as the gatekeeper to mitotic exit. APC/C activity is controlled by an interplay of multiple pathways during mitosis, including the spindle assembly checkpoint (SAC), that are not yet fully understood. Here, we show that sumoylation of the APC4 subunit of the APC/C peaks during mitosis and is critical for timely APC/C activation and anaphase onset. We have also identified a functionally important SUMO interacting motif in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 78 publications
(118 reference statements)
5
38
0
Order By: Relevance
“…With in vitro analysis of a substrate, mutants can also be particularly valuable in verifying specific modification sites. Here we describe a protocol for in vitro SUMO modification routinely used in our laboratory ( Zhu et al ., 2008 ; Reiter et al ., 2016 ), as recently illustrated by our analysis of the APC4 subunit of APC/C ( Lee et al ., 2018 ).…”
Section: [Background]supporting
confidence: 72%
See 2 more Smart Citations
“…With in vitro analysis of a substrate, mutants can also be particularly valuable in verifying specific modification sites. Here we describe a protocol for in vitro SUMO modification routinely used in our laboratory ( Zhu et al ., 2008 ; Reiter et al ., 2016 ), as recently illustrated by our analysis of the APC4 subunit of APC/C ( Lee et al ., 2018 ).…”
Section: [Background]supporting
confidence: 72%
“…To directly observe SUMO modification of specific substrates, immunoblots may also be performed with substrate-specific antibodies if modification levels are sufficiently high. For example, APC4 is a subunit of the Anaphase Promoting Complex/Cyclosome (APC/C) that is SUMO-modified robustly during the mitotic stage of the cell cycle as observed by immunoblot analysis of whole cell lysates from synchronized cells ( Lee et al ., 2018 ). Although SUMO modification by a single protein subunit can be detected as a ~12 kDa shift in molecular weight ( Figure 1 ), this shift cannot be distinguished from modification by other ubiquitin-like proteins without further validation.…”
Section: [Background]mentioning
confidence: 99%
See 1 more Smart Citation
“…Yeast SUMOylation mutants showed a large budded phenotype and fail to properly degrade APC/C substrates Pds1 and Clb3, indicating an essential role for SUMOylation during the mitotic transition 36 . Recently, APC4, one subunit of APC/ C complex, has been identified to be SUMOylated during mitosis and is required for timely anaphase onset 37,38 . Proteomic studies have also identified SUMOylation sites on other subunits of the APC/C 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Sumoylation also regulates ubiquitination enzymes in other cellular contexts. For example, sumoylation of a subunit of the APC ubiquitin E3 in mitosis was recently suggested to help activate the latter for timely anaphase onset (Eifler et al, 2018; Lee et al, 2018). Of note, SUMO and ubiquitin can also antagonize each other’s effects, sometimes via modification of the same site(s), as has been shown for DNA replication factor PCNA (Zilio et al, 2017).…”
Section: Crosstalk Between Sumo-based and Other Signaling Processesmentioning
confidence: 99%